High Prevalence of Macrolide-resistance and Molecular Characterization of Streptococcus pyogenes Isolates Circulating in China from 2009 to 2016 - Lu, Binghuai; Fang, Yujie; Fan, Yanyan; Chen, Xingchun; Wang, Junrui; Zeng, Ji; Li, Yi; Zhang, Zhijun; Huang, Lei; Li, Hongxia; Li, Dong; Zhu, Fengxia; et al. (Frontiers in Microbiology, 2017)
Streptococcus pyogenes, or group A Streptococcus, is a pathogen responsible for a wide range of clinical manifestations, from mild skin and soft tissue infections and pharyngitis to severe diseases. Its epidemiological characteristics should be comprehensively under surveillance for regulating the national prevention and treatment practice. Herein, a total of 140 S. pyogenes, including 38 invasive and 102 noninvasive isolates, were collected from infected patients in 10 tertiary general hospitals from 7 cities/provinces in China during the years 2009 to 2016. All strains were characterized by classical and molecular techniques for its emm types/subtypes, virulent factors and antibiotic resistance profiling. Of 140 isolates, 15 distinct emm types and 31 subtypes were detected, dominated by emm12 (60 isolates, 42.9%), emm1(43, 30.7%) and emm89 (10, 7.1%), and 8 new emm variant subtypes were identified. All strains, invasive or not, harboured the superantigenic genes, speB and slo. The other virulence genes, smeZ, speF and speC accounted for 96.4%, 91.4% and 87.1% of collected isolates, respectively. Further multilocus sequence typing (MLST) placed all strains into 22 individual sequence types (STs), including 4 newly-identified STs (11, 7.9%). All isolates were phenotypically susceptible to penicillin, ampicillin, cefotaxime, and vancomycin, whereas 131(93.5%), 132(94.2%), and 121(86.4%) were resistant to erythromycin, clindamycin, and tetracycline, respectively. Our study highlights high genotypic diversity and high prevalence of macrolide resistance of S. pyogenes among clinical isolates circulating in China.